Gender gaps in Peruvian scientifc research - Arroyo-Hernández, Hugo (2022)
Bibliometric studies have shown the large differences in scientificdifferences in scientific production between continents, countries or institutions. countries or institutions; however, a more thorough analysis of scientific of scientific publications has identified patterns of inequality with respect to their with respect to their authors, one of them being those related to gender. Identifying gender gaps in scientific research has become of increasing interest for the of growing interest due to the social and economic inequality it represents, because behind economic inequality that it represents, because behind them there are cultural or formativethat impede the insertion,  participation and advancement of women in the and advancement of women in the areas of science, technology and innovation.